Formulasi dan Tingkat Kesukaan terhadap Es Krim Keju dengan Menggunakan Berbagai Keju Lunak (Cream Cheese, Ricotta dan Camembert) - Layyinan Hafizha Khalish; Nuri Andarwulan; Sutrisno Koswara; Zada Agna Talitha (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Ice cream is a low temperature food product that rarely uses cheese as alternative flavor variant. This research is aimed to obtain ice cream formula with the addition of soft cheeses (cream cheese, ricotta and camembert). The basic formulation trial used the mixture of sugar (10%, 13%), skim powder (9%, 10%), milk fat (12%, 14%), and cream cheese (10, 12, 14%). The second formula trial After that, the formula trial used cream cheese, ricotta and camembert cheese as much as 7, 9 and 11% respectively into the ice cream mixture. The most acceptable formula was based on hedonic ranking and hedonic rating analysis for sample meets the proximate composition. The most acceptable formulation was composed of 12% milk fat, 9% skim powder, and 10% sugar. The trial treatment by adding 10% and 12% cream cheese yielded 70-80% overrun and the melting time. The best ice cream cheese formulation was composed of cream cheese 9%, ricotta 9% and camembert 11%. There was a significant difference in term of taste, aroma, and texture of ice cream in exception of ice cream colour. Hedonic rating showed that 9% ice cream with cream cheese was the most acceptable in term of taste, aroma and colour. These three formulas met the minimum requirements for fat content and total sugar according to the quality standard of ice cream (SNI 01-3713-1995) but it did not meet the protein standard.